An Analysis of Aisyiyah’s Islamic Educational Policies for Family and Community Empowerment: Insights from Siti Chamamah Soeratno - Iqbal Maulana; Muhammad Firdaus (At-Ta'lim : Media Informasi Pendidikan Islam, 2026)
ENGLISH: An Analysis of Aisyiyah’s Islamic Educational Policies for Family and Community Empowerment: Insights from Siti Chamamah Soeratno  Objective: This study examines Aisyiyah’s Islamic educational policies for strengthening families and communities through the cultural perspective of Siti Chamamah Soeratno. Method: Using a qualitative library research approach, the study analyzes Aisyiyah’s official documents and Chamamah’s scholarly works on Islamic education, culture, gender, and community development through content analysis. Results: The findings reveal that Aisyiyah’s policies emphasize mothers as primary educators, early Islamic character formation, community-based education, and the integration of da‘wah with social empowerment. Chamamah’s perspective reinforces these policies by positioning cultural literacy, humanistic communication, and women’s agency as essential foundations of family and community education. Conclusion: Aisyiyah’s educational policies constitute a holistic framework for empowering Muslim families and communities by integrating Islamic values, education, and cultural engagement. Contribution: This study contributes a cultural literacy perspective that enriches the discourse on Islamic educational policy, women’s educational movements, and family- and community-based Islamic education. Keywords: Islamic Educational Policy; Aisyiyah; Family-Based Education; Community Education; Siti Chamamah Soeratno.INDONESIAN: Analisis Kebijakan Pendidikan Islam Aisyiyah untuk Pemberdayaan Keluarga dan Masyarakat: Perspektif Siti Chamamah SoeratnoTujuan: Penelitian ini menganalisis kebijakan pendidikan Islam Aisyiyah dalam memperkuat keluarga dan masyarakat melalui perspektif pemikiran kultural Siti Chamamah Soeratno. Metode: Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka melalui analisis isi terhadap dokumen resmi Aisyiyah serta karya-karya Siti Chamamah Soeratno mengenai pendidikan Islam, budaya, gender, dan pengembangan masyarakat. Hasil: Temuan menunjukkan bahwa kebijakan pendidikan Aisyiyah menekankan peran ibu sebagai pendidik utama, pembentukan karakter Islami sejak dini, pendidikan berbasis komunitas, serta integrasi dakwah dengan pemberdayaan sosial. Pemikiran Chamamah memperkuat kebijakan tersebut melalui literasi budaya, komunikasi humanis, dan agensi perempuan. Kesimpulan: Kebijakan pendidikan Aisyiyah membentuk kerangka holistik bagi pemberdayaan keluarga dan masyarakat Muslim. Kontribusi: Penelitian ini memperkaya kajian kebijakan pendidikan Islam melalui perspektif literasi budaya dalam gerakan pendidikan perempuan berbasis keluarga dan komunitas.